2010
DOI: 10.1016/j.canlet.2010.04.013
|View full text |Cite
|
Sign up to set email alerts
|

miR-195, miR-455-3p and miR-10a∗ are implicated in acquired temozolomide resistance in glioblastoma multiforme cells

Abstract: Running title: miRNAs and temozolomide resistance in glioblastoma Key words: glioblastoma, resistance, microRNA,, miR-10a*, temozolomide. ABSTRACTTo identify microRNAs (miRNAs) specifically involved in the acquisition of temozolomide (TMZ) resistance in glioblastoma multiforme (GBM), we first established a resistant variant, U251R cells from TMZ-sensitive GBM cell line, U251MG. We then performed a comprehensive analysis of miRNA expressions in U251R and parental cells using miRNA microarrays. miR-195, miR-455… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(145 citation statements)
references
References 52 publications
(52 reference statements)
5
139
0
1
Order By: Relevance
“…It has been reported that STAT3-regulated miR-17 played a critical role in MAP-ERK kinase (MEK) inhibitor resistance (42), as well as that STAT3 directly increased the levels of miR-21 and miR-181b-1 (43). Currently only correlation of some specific miRNA such as miR-21 or miR-195 and temozolomide resistance were reported (44,45). We should address whether miRNAs are involved in the regulation of MGMT in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that STAT3-regulated miR-17 played a critical role in MAP-ERK kinase (MEK) inhibitor resistance (42), as well as that STAT3 directly increased the levels of miR-21 and miR-181b-1 (43). Currently only correlation of some specific miRNA such as miR-21 or miR-195 and temozolomide resistance were reported (44,45). We should address whether miRNAs are involved in the regulation of MGMT in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that miR-195, miR-455-3p and miR-10a* were the three most upregulated miRNAs in the resistant cells. When miR-195 was reduced, the resistant cells displayed a moderate cell killing effect, and the combination with TMZ strongly enhanced this effect 25 . Another article examined the correlation between the expression levels of selected microRNAs in 22 primary glioblastomas with response to concomitant therapy (e.g., chemoradiotherapy with TMZ).…”
Section: Micrornas As Biomarkers For the Diagnosis And Prognosis Of Gmentioning
confidence: 99%
“…For example, high levels of miR-21, miR-182 and miR-196 as well as low expression of miR-181b and miR-106a are associated with poor overall survival in patients with malignant gliomas [22][23][24] , and these miRNAs might function as biomarkers of glioma progression. Furthermore, miR-195, miR-455-3p, miR-10a 25 and the miR-181 family 26 have been linked to treatment resistance, and assessing the relative expression levels of these miRNAs may assist with the design of personalized treatments.…”
Section: Introductionmentioning
confidence: 99%
“…To identify miRNAs involved in TMZ resistance in GBM, Ujifuku et al. 87 used miRNA microarrays to perform a comprehensive analysis of miRNA expression in a TMZ‐sensitive GBM cell line. They found that miR‐195, miR‐455‐3p, and miR‐10a ∗ were the three most upregulated miRNAs in resistant cells.…”
Section: Introductionmentioning
confidence: 99%